Analysis Of Individual Investor Behavior At Stock Market Study Group Member Of University In Surakarta Using Analytical Hierarchy Process Method (AHP) - Sari, Cahyani Tunggal; Wardhani, Bernadeta Anindya Nandi (Economics and Business Solutions Journal, 2018)
Behavioral finance is a new approach to financial markets. Behavioral finance argues that some financial phenomena can be understood sensibly by using a model in which some agents are not entirely rational. The Market Efficiency Theory or known as the EMH (Efficient Market Hypothesis) was introduced by Fama (1970), on the ground EMH said that in an efficient capital market, relevant information will be responded quickly, completely and accurately by the market. If the market is efficient, then all information is reflected in the price. The price will adjust quickly and precisely to new information, and no one "precedes the market", which means that in an efficient capital market there should be no one getting excessive results because it has better access to information and responds more quickly. The purpose of this study is to determine the factors that most influence the investment decision of individual investors in the universities in Surakarta. This study used the Analitycal Hierarchy Process (AHP) method and distributed questionnaires to individual investors to find out the factors that influence them in trading. This research was conducted at Capital Market Study Group in the Higher Education Area of Surakarta Residence. The population in this research is Stock Market Study Group at Universities in Surakarta, while the affordable population is 5 Universities who have the Capital Market Study Group each taken as many as 20 respondents. The sampling technique used stratified random sampling technique, that is, taking a random sample of proportional from each group in each college in Surakarta.The result shows that Long-Term Investment has 56% priority to be choosen as investment, Short-Term Investment has 29% priority to be choosen as investment, and Mid-Term Investment has 15% priority to be choosen as investment.